Dengue virus NS1 protein conveys pro‐inflammatory signals by docking onto high‐density lipoproteins. (24th May 2022) - Benfrid, Souheyla; Park, Kyu‐Ho; Dellarole, Mariano; Voss, James E; Tamietti, Carole; Pehau‐Arnaudet, Gérard; Raynal, Bertrand; Brûlé, Sébastien; England, Patrick; Zhang, Xiaokang; Mikhailova, Anastassia; Hasan, Milena; et al.
Abstract: The dengue virus nonstructural protein 1 (NS1) is a secreted virulence factor that modulates complement, activates immune cells and alters endothelial barriers. The molecular basis of these events remains incompletely understood. Here we describe a functional high affinity complex formed between NS1 and human high‐density lipoproteins (HDL). Collapse of the soluble NS1 hexamer upon binding to the lipoprotein particle leads to the anchoring of amphipathic NS1 dimeric subunits into the HDL outer layer. The stable complex can be visualized by electron microscopy as a spherical HDL with rod‐shaped NS1 dimers protruding from the surface. We further show that the assembly of NS1‐HDL complexes triggers the production of pro‐inflammatory cytokines in human primary macrophages while NS1 or HDL alone do not. Finally, we detect NS1 in complex with HDL and low‐density lipoprotein (LDL) particles in the plasma of hospitalized dengue patients and observe NS1‐apolipoprotein E‐positive complexes accumulating overtime. The functional reprogramming of endogenous lipoprotein particles by NS1 as a means to exacerbate systemic inflammation during viral infection provides a new paradigm in dengue pathogenesis. Synopsis: The dengue virus NS1 protein forms stable complexes with high‐density lipoprotein (HDL) and low‐density lipoprotein particles, which are detectable in the plasma of severe dengue patients. NS1‐HDL complexes trigger pro‐inflammatory signals in human primary macrophages. DENV NS1 binds human HDL and LDL particles to form stable complexes. Hexameric NS1 fuses with the surface of HDL and disassembles into dimeric rods. NS1‐HDL complexes induce the production of cytokines in human primary macrophages. NS1 forms high molecular weight complexes with apolipoproteins in DENV‐infected patients. Abstract : The dengue virus NS1 protein and high‐density lipoproteins form functional high‐affinity complexes that are detectable in patient plasma and induce inflammatory signals in human primary macrophages. NS1 also interacts with other types of lipoprotein particles.